Improved Carotid Elasticity but Altered Central Hemodynamics and Carotid Structure in Young Athletes - Lisa Baumgartner; Heidi Weberruß; Katharina Appel; Tobias Engl; Daniel Goeder; Renate Oberhoffer-Fritz; Thorsten Schulz (Frontiers in Sports and Active Living, 2021)
Young athletes most often exceed the physical activity recommendations of the World Health Organization. Therefore, they are of special interest for investigating cardiovascular adaptions to exercise. This study aimed to examine the arterial structure and function of young athletes 12–17 years old and compare these parameters to reference values of healthy cohorts. Carotid intima-media thickness (cIMT), carotid diameter, cIMT÷carotid diameter-ratio (cIDR), arterial compliance (AC), elastic modulus (Ep), β stiffness index (β), and carotid pulse wave velocity (PWVβ) were determined using ultrasound in 331 young athletes (77 girls; mean age, 14.6 ± 1.30 years). Central systolic blood pressure (cSBP) and aortic PWV (aPWV) were measured using the oscillometric device Mobil-O-Graph. Standard deviation scores (SDS) of all parameters were calculated according to German reference values. The 75th and 90th percentiles were defined as the threshold for elevated cIMT and arterial stiffness, respectively. Activity behavior was assessed with the MoMo physical activity questionnaire, and maximum power output with a standard cardiopulmonary exercise test. One-sample t-tests were performed to investigate the significant deviations in SDS values compared to the value “0”. All subjects participated in competitive sports for at least 6 h per week (565.6 ± 206.0 min/week). Of the 331 young athletes, 135 (40.2%) had cIMT >75th percentile, 71 (21.5%) had cSBP >90th percentile, and 94 (28.4%) had aPWV>90th percentile. We observed higher cIMT SDS (p < 0.001), cIDR SDS (p = 0.009), and AC SDS (p < 0.001) but lower β SDS (p < 0.001), Ep SDS (p < 0.001), and PWVβ SDS (p < 0.001) compared to the reference cohort. The cSBP SDS (p < 0.001) and aPWV SDS (p < 0.001) were elevated. In conclusion, cIMT and cIDR were higher in young athletes than in a reference cohort. Furthermore, young athletes presented better carotid elasticity and lower arterial stiffness of the carotid artery. However, central arterial stiffness was higher compared to the reference cohort. The thickening of the carotid intima-media complex in combination with a reduction in arterial stiffness indicates a physiological adaptation to exercise in youth.